1991
DOI: 10.1073/pnas.88.21.9453
|View full text |Cite|
|
Sign up to set email alerts
|

Brain and heart sodium channel subtype mRNA expression in rat cerebral cortex.

Abstract: The expression of mRNAs coding for the a subunit of rat brain and rat heart sodium channels has been studied in adult and neonatal rat cerebral cortex using the reverse transcription-polymerase chain reaction (RT-PCR). Rat brain sodium channel subtype I, H, HA, and HI sequences were simultaneously amplified in the same PCR using a single oligonucleotide primer pair matched to all four subtype sequences. Identification of each subtype-specific product was inferred from the appearance of unique fragments when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…that study, preliminary experiments noted heart-type Na ϩ channel ␣-subunit mRNA in primary cultures of rat cortical astrocytes (Yarowsky et al, 1991). Hartmann et al (1996) also detected a cardiac-like Na ϩ channel mRNA in limbic system structures from rat brain, and patch clamp studies have shown that entorhinal cortex (White et al, 1993) and septal neurons (Hartmann et al, 1996) express a Na ϩ current, which is Zn 2ϩ sensitive, similar to cardiac Na ϩ channels (Frelin et al, 1986;Ravindran et al, 1991;Visentin et al, 1990).…”
Section: Discussionmentioning
confidence: 92%
“…that study, preliminary experiments noted heart-type Na ϩ channel ␣-subunit mRNA in primary cultures of rat cortical astrocytes (Yarowsky et al, 1991). Hartmann et al (1996) also detected a cardiac-like Na ϩ channel mRNA in limbic system structures from rat brain, and patch clamp studies have shown that entorhinal cortex (White et al, 1993) and septal neurons (Hartmann et al, 1996) express a Na ϩ current, which is Zn 2ϩ sensitive, similar to cardiac Na ϩ channels (Frelin et al, 1986;Ravindran et al, 1991;Visentin et al, 1990).…”
Section: Discussionmentioning
confidence: 92%
“…In the periphery, rNa v 1.5 is expressed in denervated muscle [34] and in a peripheral neurotumourderived cell line RT4-B8 [53]. In the CNS rNa v 1.5 has been detected at the molecular level in rat cortex [52] and spinal cord astrocytes [4] and described functionally as well as molecularly in a neuroblastoma cell line [16]. rNa v 1.5 mRNA is thought to be restricted to the limbic region [17], which is the well-known epileptic focus for some types of seizures.…”
Section: Methodsmentioning
confidence: 97%
“…Sodium channel ␣ and ␤ subunits show a defined temporal and spatial distribution in the rat central nervous system (CNS) revealed by immunoprecipitation (Gordon et al, 1987), Northern blot analysis (Beckh et al, 1989), reverse transcriptase-polymerase chain reaction (RT-PCR; Yarowsky et al, 1991), in situ hybridisation (Brysch et al, 1991;Furuyama et al, 1993;Black et al, 1994;Schaller et al, 1995;Felts et al, 1997;Gastaldi et al, 1997Gastaldi et al, , 1998Levy-Mozziconacci et al, 1998), and immunohistochemistry (Westenbroek et al, 1989). These studies show that the expression of sodium channel type I begins to increase after birth and, in the adult, is highest in caudal regions (e.g., colliculus and medulla pons) of the CNS.…”
mentioning
confidence: 99%